Sustainable Utilization of Agricultural Waste: Formulation of an Antioxidant Face Gel from Coconut Husk, Pineapple Peel, and Watermelon Rind - Mustaffa, Fazlina; Sahgal, Geethaa; Ameerdin, Mohamed Asem; Rajavel, Varatharajan; Mogan, Dhivyasri; Xuan, Wong Wan; Asokumar, Keerthana (Free Radicals and Antioxidants, 2025)
Background: The increasing generation of waste product has become a main environmental concern worldwide, especially due to the disposal of fruit residues such as rinds and peels. These agricultural by-products are rich sources of bioactive phytochemicals including phenolic compounds and flavonoids with potential antioxidant and cosmetic applications. The present study aimed to formulate and evaluate a moisturizing antioxidant face gel using extracts from watermelon rind (Citrullus lanatus), pineapple peel (Ananas comosus), and coconut husk (Cocos nucifera) as a sustainable waste management approach. Materials and Methods: Fruit peels were extracted using 96% ethanol through maceration, and the Total Phenolic Content (TPC) of the extracts was determined using the Folin-Ciocalteu method. Three gel formulations containing 1%, 2%, and 3% fruit peel extracts were prepared using Carbopol as a gelling agent and evaluated for physicochemical properties including stability, spreadability, gel strength, washability, and pH. Accelerated stability tests indicated that all formulations remained stable with no phase separation and maintained acceptable pH and homogeneity. Results: Among the extracts, coconut husk demonstrated the highest phenolic content (66 mg GAE/g), followed by pineapple peel and watermelon rind. In vivo evaluation using Sprague Dawley rats showed that the gel formulation containing 1% extract significantly improved skin moisture levels compared to the control group (p<0.05) without causing skin irritation. Conclusion: These findings suggest that fruit peel waste possesses significant antioxidant potential and can be utilized as a sustainable raw material for the development of skincare formulations while efficiently managing the agricultural food waste.
Keywords: Agricultural Waste; Antioxidant Face Gel; Coconut Husk; Cosmetic Formulation; Flavonoids; Natural Antioxidants; Phenolic Compounds; Pineapple Peel; Skin Hydration; Sustainable Utilization; Waste Valorization; Watermelon Rind